CMC- Banana Flour film: production & characterization: article / Arina Izzati Ab Rahman and Fariza Hamidon - Ab Rahman, Arina Izzati; Hamidon, Fariza (2019)
A study has been conducted to produce edible films from banana flour and carboxylmethyl cellulose (CMC) with addition of glycerol as plasticizer. The CMC-banana flour films were synthesized by casting method with different CMC concentrations (0, 5, 10 and 15% w/w). The characterization of the film is made based on mechanical strength, solubility, water vapor permeability (WVP), color and Fourier Transform Infrared Spectroscopy (FTIR). The thicknesses of the films range between 0.133±0.05 to 0.165±0.09 mm. As CMC is added into banana film from 0 to 10% w/w, the increase in tensile strength (TS) were found with the range of 1.86±0.08MPa to 1.99±0.26MPa and reduced upon the addition of 15%CMC and this trend was similar to the elongation at break (EAB) of the film. The CMC-banana films have the solubility range from 41.39±0.19 to 50.55±6.16% and this study found that the solubility of the film reduced in addition of CMC between 5% to 15% and increase in solubility with temperature (25, 37 and 90°C). WVP in the CMC-banana films is reduced in 5%CMC addition (3.7±0.16 x10-9 g.mm/(h.cm².Pa) and keep increasing until 5.24±0.08 x109 g.mm/(h.cm².Pa). Overall, the films form brownish color due to natural content of banana flour used in the film production with slightly different opacity due to the difference in CMC concentrations. All the parameters of films were compared with other natural sources of edible film and it is believed that CMCbanana flour film applicable to certain type of food packaging applications.